Tribute to Prof Gunther H. Wittenberg, 5 April 1935 - 29 March 2014 - Farisani, Elelwani (Old Testament essays, 2014)
Gunther Hermann Wittenberg was born to missionary parents on 5 April 1935 near Lake Victoria, Tanzania. Gunther met his wife, Monika Teichler, in Germany. They married in 1961 and had four children: Martin, Inge, Gertrud and Reinhild. He first enrolled for a B.A. in Pietermaritzburg before moving to Germany to study theology in Bethel, Heidelberg, Tübingen and Kiel. Gunther was ordained a Lutheran pastor in 1963. He died at home on 29 March 2014 of the cancer of the pancreas.